Addition of B-Type Natriuretic Peptide to Existing Clinical Risk Scores Enhances Identification of Patients at Risk for Atrial Fibrillation Recurrence After Pulmonary Vein Isolation. Issue 4 (December 2015) - Shaikh, Amir Y.; Esa, Nada; Martin-Doyle, William; Kinno, Menhel; Nieto, Iryna; Floyd, Kevin C.; Browning, Clifford; Ennis, Cynthia; Donahue, J. Kevin; Rosenthal, Lawrence S.; McManus, David D.
Abstract : Introduction: Predicting which patients will be free from atrial fibrillation (AF) after pulmonary vein isolation (PVI) remains challenging. Clinical risk prediction scores show modest ability to identify patients at risk for AF recurrence after PVI. B-type natriuretic peptide (BNP) is associated with risk for incident and recurrent AF but is not currently included in existing AF risk scores. We sought to evaluate the incremental benefit of adding preoperative BNP to existing risk scores for predicting AF recurrence during the 6 months after PVI. Methods: One hundred sixty-one patients with paroxysmal or persistent AF underwent an index PVI procedure between 2010 and 2013; 77 patients (48%) had late AF recurrence after PVI (>3 months post-PVI) over the 6-month follow-up period. Results: A BNP greater than or equal to 100 pg/dL ( P = 0.01) and AF recurrence within 3 months after PVI ( P < 0.001) were associated with late AF recurrence in multivariate analyses. Addition of BNP to existing clinical risk scores significantly improved the areas under the curve for each score, with an integrated discrimination improvement of 0.08 ( P = 0.001) and a net reclassification improvement of 60% ( P = 0.001) for all risk scores. Conclusions: Circulating BNP levels are independently associated with late AF recurrence after PVI. Inclusion of BNP significantly improves the discriminative ability of CHADS2, CHA2DS2-VASc, R2CHADS2, and the HATCH score in predicting clinically significant, late AF recurrence after PVI and should be incorporated in decision-making algorithms for management of AF. B-R2CHADS2 is the best score model for prediction of late AF recurrence.